2008
DOI: 10.1002/hed.20760
|View full text |Cite
|
Sign up to set email alerts
|

Trismus in patients with oropharyngeal cancer: Relationship with dose in structures of mastication apparatus

Abstract: Patients treated with brachytherapy received a lower dose in masticatory muscles. A steep dose-effect relationship between mean dose in masseter muscle and pterygoid muscles and the probability of having trismus complaints was observed; with every additional 10 Gy to the pterygoid muscle, an increase of the probability of trismus of 24% was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 29 publications
4
101
0
2
Order By: Relevance
“…Only a few studies have investigated the relationship between radiation doses and mouth opening/trismus [20,27,28]. In our prospective study a significant correlation was found between the measured and the perceived mouth opening, and the radiation doses to most mastication structures.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Only a few studies have investigated the relationship between radiation doses and mouth opening/trismus [20,27,28]. In our prospective study a significant correlation was found between the measured and the perceived mouth opening, and the radiation doses to most mastication structures.…”
Section: Discussionmentioning
confidence: 52%
“…Teguh et al, who retrospectively analyzed 56 patients with oropharyngeal cancer by means of quality of life questionnaires, concluded that there was a steep dose relationship between the mean doses to the masseter and pterygoid muscles [20]. This result is not surprising, because these two structures are most adjacent to the nasopharynx, oral cavity, and oropharynx area (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The probability of developing trismus is reported to increase 24% for every 10 Gy of additional radiation over 40 Gy delivered to the pterygoid muscles. 17 Althogh a few authors state that restriction of mouth opening may occur even at low doses of irradiation, 18 a steep dose effect relationship between radiation dose to the masticatory apparatus and trismus has been noted. 19,20 The high incidence of trismus in our study can be attributed to the use of external beam radiotherapy because trismus with conventional radiotherapy is reported to be 25.4%.…”
Section: Discussionmentioning
confidence: 99%
“…13 Our study proves that mouth opening values show statistically significant changes with good patient compliance to physiotherapy (p = 0.02), and the gains that can be made when patients are motivated. Various methods of treatment of trismus that have been reported include use of supportive measures like regular use of muscle relaxants or hot fomentation, hyperbaric oxygen or oral medication such as pentoxiphylline, 17 isometric and range of motion exercises, use of mechanical aids like rubber plugs, wooden tongue blades, spatulas, the TheraBite device, 14,24 and dynamic splinting. Passive exercises had better role in the management and prevention of trismus than active exercises as seen in literature.…”
mentioning
confidence: 99%